2000
DOI: 10.1080/00223980009600846
|View full text |Cite
|
Sign up to set email alerts
|

Perception of Parental Acceptance in Women With Binge Eating Disorder

Abstract: The authors contribute to the validating literature for binge eating disorder (BED) by examining perceptions of parents and satisfaction with life among obese women with and without BED. Participants were female patients, recruited through a private medical clinic, who were assigned to groups on the basis of body mass index (BMI) and scores on the Questionnaire on Eating and Weight Patterns (QEWP; R. L. Spitzer et al., 1992). Groups consisted of (a) obese women with BED (n = 32), (b) obese women who had no eat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 39 publications
4
22
0
Order By: Relevance
“…Additionally, obese BED patients report lower HRQOL than obese non-BED patients. 51,53 Further, women with BED generally report functional impairment at similar levels to groups of eating disorder patients. 40 Finally, disease-specific HRQOL instruments have shown a similar pattern of results: obese BED patients report greater impairments than obese non-BED patients in overall HRQOL, as well in a variety of specific domains of HRQOL.…”
Section: Studies Of Health-related Quality Of Life (Hrqol) Life Satimentioning
confidence: 93%
See 1 more Smart Citation
“…Additionally, obese BED patients report lower HRQOL than obese non-BED patients. 51,53 Further, women with BED generally report functional impairment at similar levels to groups of eating disorder patients. 40 Finally, disease-specific HRQOL instruments have shown a similar pattern of results: obese BED patients report greater impairments than obese non-BED patients in overall HRQOL, as well in a variety of specific domains of HRQOL.…”
Section: Studies Of Health-related Quality Of Life (Hrqol) Life Satimentioning
confidence: 93%
“…[51][52][53][54][55] Masheb and Grilo 54 reported that BED participants have considerably impaired scores on the SF-36 Health Survey compared to those seen in U.S. norms. Additionally, obese BED patients report lower HRQOL than obese non-BED patients.…”
Section: Studies Of Health-related Quality Of Life (Hrqol) Life Satimentioning
confidence: 95%
“…Studies supporting this conclusion tend to deal with the following issues among children, adolescents, and adults: (1) personality and psychological adjustment problems (Ahmed, Rohner, & Carrasco, 2012;Amato, 1994;Dominy, Johnson, & Koch, 2000;Khaleque & Rohner, 2011;Komarovsky, 1976;Stagner, 1938); (2) mental illness (Akun, 2016;Barrera Jr. & Garrison-Jones, 1992;Lefkowitz & Tesiny, 1984); (3) psychological health and well-being (Amato, 1994); (4) conduct disorder (Eron, Banta, Walder, & Laulicht, 1961;Putnick et al, 2014); (5) substance abuse (Brook & Brook, 1988;Emmelkamp & Heeres, 1988); (6) delinquency (Andry, 1962); (7) prosocial behavior (Putnick et al, 2014); (8) children's social competence (Putnick et al, 2014); and (9) school performance (Putnick et al, 2014).…”
Section: The Importance Of Father Lovementioning
confidence: 99%
“…Since the publication of DSM-IV [3], binge eating disorder has been included in the eating disorders section as an eating disorder not otherwise specified (EDNOS), that is, a category including the disorders that do not meet the criteria for AN or BN. With respect to epidemiologic studies on binge eating, it has been found to be significantly more common among females than males (46% vs. 30%), and among binging-compensating (BC) individuals (who compensate binge eating with practice aimed at weight loss, such as using laxatives) [1,4].…”
Section: Introductionmentioning
confidence: 99%
“…Several empirical studies have stressed the role that family context plays in the development and maintenance of eating disorders among adolescents [1]. The research has mostly drawn attention to anorexia nervosa (AN) and bulimia nervosa (BN), but there have been relatively few studies on binge eating disorders (BED).…”
Section: Introductionmentioning
confidence: 99%